Development of an Acute Femoral Hernia Treatment Algorithm: Insights From the ACHQC National Database - Kim, Ian; Barmparas, Galinos; Towfigh, Shirin (The American surgeon, 2025)
BackgroundDue to the rarity of femoral hernias (FH), mastery of surgical decision-making can be challenging. Current guidelines address only elective treatment of FH, without guidance for the acute setting.ObjectiveTo review current surgical management of FH, and to determine a modern-day treatment algorithm for FH in the acute setting.MethodsThe Abdominal Core Health Quality Collaborative (ACHQC) was surveyed for adult patients undergoing elective (EFH) or acute (AFH) FH repair from 2016 to 2023.ResultsOf 2563 FH repairs, 61 (2.4%) were AFH. Patients with AFH were more likely to be female (68.9% vs 31.1%, < 0.01), older (median age 76 vs 64.5 years, < 0.01), have greater comorbidity (ASA III or higher, 58% vs 30%, < 0.01), and larger hernia defects (≥1.5 cm, 51% vs 34%, < 0.01). Open surgery was the predominant approach for AFH (61% vs 14%, < 0.01), while EFH was mostly repaired robotically (54% vs 10%, < 0.01). Over time, robotic surgery increased for both AFH and EFH. AFH were less likely to have mesh implanted (72% vs 97%, < 0.01), though permanent synthetic mesh remained the dominant choice in both groups (89% vs 98%, < 0.01).DiscussionOpen surgery with mesh dominates for AFH, but robotic techniques are increasingly utilized. A treatment algorithm is proposed to optimize management of patients with AFH to determine the safest approach based on clinical scenarios.